Efektivitas ROM Aktif-Asistif: Spherical dan Cylindrical Grip terhadap Kekuatan Otot Pasien Stroke - Herliza; Dodi Efrisnal; Liza Fitri Lina (LPPM Universitas Muhammadiyah Riau, 2022)
Stroke is a major health problem in both developed and developing countries. Stroke results in suffering to the sufferer, the social and economic burden for families and sufferers, communities, and the state. The purpose of this study was to investigate the effect of active-asistive range of motion (ROM): spherical grip and cylindrical grip on increasing muscle strength of upper limb in stroke patients. In this study quantitative with analytic approach. The research design used is pre experiment one group pre- test and post-test design. Research result 16 respondents before spherical grip therapy was found that the highest frequency of upper limb muscle strength 5 people (31,3%) with score 1 and 2 was on palpation contraction intervention, but no movement was seen, there was movement but could not fight . While after spherical grip therapy found that the highest frequency of upper extremity muscle strength 6 people (37,5%) with score 2 that is at intervention there is movement, but can not fight. Of the 16 respondents prior to cylindrical grip therapy it was found that the highest frequency of upper extremity muscle strength was 6 people (37.5%) with score 1 in the intervention of palpation contraction, but no visible movement. Meanwhile, after cylindrical grip therapy, it was found that the highest frequency of upper limb muscle strength 7 people (43,8%) with score 2 was intervention movement but not resistance. Range of Motion (ROM) Active-Assistive: Spherical Grip and Cylindrical Grip Effective to increase muscle strength of upper limb in stroke patient at Dr. Hospital. M. Yunus of Bengkulu Province. To be used as a reference and information for health workers, especially Dr. Hospital. M. Yunus Bengkulu Province so much better in dealing with patients with stroke patients.